Back Pain In The Third Trimester Of Pregnant Women Assessed From The Level Of Stress And Physical Activity In Lambangan Village, Pagimana District - Wulandari, Anggrawati; Retno Palupi Yonni Siwi; Putri Eka Sejati; Epi Ardiana (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2023)
During pregnancy, women will experience changes both anatomical, physiological and psychological, causing discomfort during pregnancy. One of the discomforts that pregnant women often experience is back pain. Back pain is pain felt in the vertebral area, mainly arising from excessive bending, lifting heavy loads, or previous experiences of back pain. Back pain can be mild to severe, disrupting the activities of pregnant women. The aim of this study was to analyze the relationship between back pain in third trimester pregnant women in terms of stress levels and physical activity in Lambangan Village, Pagimana District.. This research uses designCorrelational Analytics And Time approachCross sectional. The samples in this study were some pregnant women in the third trimesterLambangan Village, Pagimana District by a total of 30 respondents. The sampling method in this research uses the technique Accidental Sampling. Data collection using questionnaires. The results of data analysis to see the relationship between the independent variable and the dependent variable using statistical testsUji Spearman Rank with a significant level of α = 0.05. The research results showed that of the 30 respondents, the majority of respondents had normal stress levels, by total of 19 respondents (63.3%), half of the respondents had light physical activity, by total of 15 respondents (50.0%), half of the respondents experienced back pain. mild, by a total of 15 respondents (50.0%). Results of data analysis using statistical testsSpearman Rank obtained a P value < α 0.05 (0.000 < 0.05), then H0 is rejected and H1 is accepted, which means that there is a relationship between stress levels and back pain in third trimester pregnant women and there is a relationship between physical activity with back pain in third trimester pregnant women in Lambangan Village, Pagimana District with valuesP value < α 0,05 (0.000 < 0,05) Normal stress levels and activity The mild physical condition of pregnant women can influence the occurrence of mild back pain.